The Relationship between Stunting and Body Resistance to Infection in Children: A Literature Review - Candra, Aisyah; Handini, Laksmi Suci (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Background: Stunting is a chronic nutritional problem due to malnutrition, especially during the first 1,000 days of life. In addition to affecting physical growth, stunting also affects children's cognitive development and immune system. Stunted children have a higher risk of recurrent infections such as respiratory infections and diarrhea, because their immune systems are not yet optimally developed. In Indonesia, the prevalence of stunting is still quite high and is one of the main health problems, caused by prolonged malnutrition that weakens the function of the child's immune system. Objective: To determine the relationship between stunting and resistance to infection in children, as well as the role of proper nutrition in improving health and endurance. Methods: A literature review covering various scientific sources from 2019-2024 through the Google Scholar, PubMed, and Science Direct databases with the keywords